The effectiveness of semantic intervention for word-finding difficulties in college-aged students (16–19 years) with persistent Language Disorder. (August 2019) - Campbell, Lisa; Nicoll, Hilary; Ebbels, Susan H
Background and aims: Little evidence exists for the effectiveness of intervention for older adolescents and young adults with language disorders, particularly for those over 16 years. This study involves college-aged students aged 16–19 years with Language Disorder and Word-Finding Difficulties and investigates whether progress in word finding following 1:1 semantic intervention is greater than progress during a baseline period as measured by a standardised test. Methods: Twenty-five college-aged students (20 males and 5 females) with Language Disorder and Word-Finding Difficulties (aged 16;4–18;4 years) participated in a single baseline design study comparing progress on the Test of Adolescent and Adult Word Finding during an intervention period with progress during a baseline period of equal length. Intervention was focused on semantics of different words from those in the Test of Adolescent and Adult Word Finding and was delivered 1:1 by the participants' usual Speech and Language Therapist, 30 minutes per week, for eight weeks. Results: The participants made significant progress in raw score on the Test of Adolescent and Adult Word Finding during both the baseline ( d  = 1.4) and intervention ( d  = 2.5) periods, but progress during the intervention period was significantly greater than during the baseline period ( d  = 1.16). Individual data showed reliable change for five participants during the baseline period and for 20 participants during the intervention period. At the start of the study, all participants had standard scores below 85, but after intervention, 10/25 participants scored above 85. Conclusions: Four hours of semantic intervention led to significantly greater gains on a standardised test of word finding than during a baseline period of equal length in 16–19 year olds with Language Disorder and Word-Finding Difficulties. The words in the standardised test had not been included in the intervention, indicating generalised gains. Implications: This study shows that intervention (at least for Word-Finding Difficulties) can be effective for this older age group of college-aged students with Language Disorder and therefore the effectiveness of Speech and Language Therapy services for this age group in a wider range of areas of language should also be investigated.